Problems and Prospects of Women Entrepreneurship in Nepal - Bhatta, Ghanshyam (Journal of Durgalaxmi, 2022)
Entrepreneurship plays a key role in the economic development of the nation. It leads to the creation of capital as well as the generation of social benefits. It has incredible possibilities in exploring women's potential which could directly contribute to the national economy through women entrepreneurship. Due to the growing industrialization, urbanization, communication, social legislation and higher education and awareness, the emergence of women-owned business is increasing rapidly in the economies of almost all countries. The present paper endeavors to examine the problems faced by women entrepreneurs and to make suggestions for future prospects for the development of women entrepreneurs in Nepal. This paper is based on secondary data and an extensive literature review is carried out on problems faced by women entrepreneurs. At the end, this paper recommends addressing problems of women entrepreneurship from the Nepalese perspective. The result of this article indicates that government and policy makers should play their role toward preventing gender discrimination and domestic violence against women and upholding their right to work for women entrepreneurs. They should develop effective policies, rules and regulations to enhance women entrepreneurship. Finally, the researcher recommends establishing institutions for advocating the right of women entrepreneurs that provides social awareness against discrimination of women.